SISTEM INFORMASI ABSENSI HARIAN SMPN 01 ABUNG TINGGI MENGGUNAKAN METODE WATERFALL UNTUK MENINGKATKAN KEDISIPLINAN SISWA - Yuntriani, Yuntriani; Hasyim, Ahmad Kori (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2019)
Usefulness of this absence occurs on the part of the student and the pengada learning process. One of the usefulness of this absence to the public among others is in the calculation of the possibility of employees in attendance and one of the usefulness of this attendance information to the principal, among others, to evaluate a service and the quality of teachers at SMPN 01 Abung Tinggi and making benchmarks forward to provide better knowledge. Taking this attendance data yourself manually has many drawbacks, such as invalid data when incoming data is wrong. Another drawback of retrieving data manually is the missing or corrupted data. Another drawback is the lack of efficiency and effectiveness in data processing. At SMPN 01 Abung Tinggi, the daily absence system that runs still manual so that there will be manipulation of data in attendance system, in this case the author tries to take advantage of the rapid development of technology, especially progress in the field of information technology, especially on computer technology. In examining a problem there must be a problem, and to avoid problems encountered, the authors limit the problem in the preparation of this thesis, just data recording, input data and create daily absence report SMPN 01 Abung Tinggi Lampung Utara, this study in accordance with the intent and goals to be achieved or right on the target is to facilitate employees in the process of making reports and leaders, making a computerized system well to simplify In the absence of data processing and designing data processing system daily attendance at SMPN 01 Abung Tinggi Kotabumi North Lampung.